Genetic regions that interact with loss- and gain-of-function phenotypes of deltex implicate novel genes in Drosophila Notch signaling. - Hori, K.; Fuwa, T.J.; Seki, T.; Matsuno, K. (Molecular Genetics and Genomics, 2005)
The Notch signaling pathway is an evolutionarily conserved mechanism that regulates many cell fate decisions. The deltex (dx) gene encodes an E3-ubiquitin ligase that binds to the intracellular domain of the Notch protein and regulates Notch signaling in a positive manner. However, it is still not clear how Dx does this. We generated a transgenic line, GMR-dx, which overexpresses dx in the developing Drosophila eye disc. The GMR-dx line showed a rough-eye phenotype, specific transformation of a photoreceptor cell (R3 to R4), and a rotation defect in the ommatidia. This phenotype was suppressed in combination with a dx loss-of-function mutant, indicating that it was due to a dx gain-of-function. We previously reported that overexpression of Dx results in the stabilization of Notch in late endosomes. Here, we found that three motifs in Dx, a region that binds to Notch, a proline-rich motif and a RING-H2 finger, were required for this stabilization, although the relative activity of these variants in this assay did not always correspond to the severity of the rough-eye phenotype. In an attempt to identify novel genes of the Notch pathway, we tested a large collection of chromosomal deficiencies for the ability to modify the eye phenotypes of the GMR-dx line. Twelve genomic segments that enhanced the rough-eye phenotype of GMR-dx were identified. To evaluate the specificity of these interactions, we then determined whether the deletions also interacted with the wing phenotypes associated with a loss-of-function mutation of dx, dx24. Analyses based on whole-genome information allowed us to conclude that we have identified two novel loci that probably include uncharacterized genes involved in Dx-mediated Notch signaling.